FORMATION OF SCIENTIFIC RESEARCH COMPETENCIES OF LAW STUDENTS - Bobkova, Antonina; Vitvitskyi, Serhii; Zakharchenko, Andrii; Nikolenko, Liudmyla; Katrych, Anastasiia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The practical activity of a lawyer involves a comprehensive analysis of various legal situations, the search for optimal ways to resolve them, the use of analogies, generalization, development and substantiation of new legal positions (including based on doctrinal sources), that is, it contains elements of the researcher's work. With this in mind, one of the important components in teaching legal students is the formation of their research competencies. The purpose of this study is to prepare proposals for improving approaches to the formation of scientific research competencies of students of legal specialties. During the research, formal legal, sociological and other methods of scientific knowledge were used. As a result of the study, proposals were substantiated for the formation of scientific research competencies of law students, based on the logic of scientific research in the field of law. These proposals imply consistent training of law students to work with facts of reality, scientific facts, scientific problems and scientific hypotheses, using appropriate methods of scientific knowledge.